2013
DOI: 10.1093/annonc/mdt289
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pixantrone-based regimen (CPOP-R) with doxorubicin-based therapy (CHOP-R) for treatment of diffuse large B-cell lymphoma

Abstract: CPOP-R is an active regimen with modestly lower response rates than CHOP-R but similar PFS and event-free survival. This study demonstrates a substantially lower cardiotoxicity of pixantrone compared with doxorubicin when used as first-line therapy in DLBCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 11 publications
1
41
0
2
Order By: Relevance
“…Later, Herbrecht et al [32] reported a randomized Phase II in an upfront setting where Pixantrone was combined with Cyclophosphamide, Vincristine and prednisolone (R-CPOP) and compared to standard R-CHOP. The CR rate (75 vs 84%) and duration was noninferior to R-CHOP.…”
Section: Combination Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Herbrecht et al [32] reported a randomized Phase II in an upfront setting where Pixantrone was combined with Cyclophosphamide, Vincristine and prednisolone (R-CPOP) and compared to standard R-CHOP. The CR rate (75 vs 84%) and duration was noninferior to R-CHOP.…”
Section: Combination Therapymentioning
confidence: 99%
“…While Pixantrone cannot replace Doxorubicin in the upfront setting for all patients, the major reduction in cardiac side effects observed in the upfront trial [32] suggests this drug could offer an interesting alternative to Doxorubicin when anthracyclines are contra indicated. This is typically the case in the frail-elderly population.…”
Section: Expert Opinionmentioning
confidence: 99%
“…The problem of cardiotoxic agents in the treatment of comorbid patients with DLBCL is addressed by several recently published trials. The R-BL regimen might be an alternative treatment option, in addition to regimens with low-dose anthracyclines (Peyrade et al, 2011;Merli et al, 2012), regimens with less cardiotoxic agents, such as pixantrone, or the combination regimen with rituximab, cyclophosphamide, vincristine, gemcitabine and prednisone in patients with coexisting cardiac disease (Luminari et al, 2010;Herbrecht et al, 2013;Fields et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, both of these drugs are approved for use only under limited conditions, and comprehensive clinical comparisons with DOX or other anthracyclines are limited [1]. Pixantrone was less cardiotoxic than DOX in a phase II study on patients with newly diagnosed non-Hodgkin lymphoma [29]. Pixantrone was also reasonably cardiac-tolerable in patients with refractory/relapsed non-Hodgkin lymphoma that had been previously treated with DOX [30].…”
Section: Primary Prevention Of Anthracycline Cardiotoxicitymentioning
confidence: 99%